Cost Efficiency of Chinese Commercial Banks - A Stochastic Frontier Analysis - LI, YAJING (2015)
This study estimates the cost efficiency of Chinese commercial banks by employing stochastic frontier analysis. The main objective is to assess cost efficiency by applying the most recent post-reform data from 2004 to 2014. A two-stage regression model is used to examine the impact from potential influential factors on cost efficiency. Overall, the estimated cost efficiency is 77.75% compared with “best practice” banks in the selected sample. Foreign-owned commercial banks are found to be the most efficient. Macroeconomic factors do not show a significant influence on cost efficiency. A positive correlation between bank size, return on assets (ROA) and equity ratio is found, and the loan-deposit ratio is negatively related to cost efficiency.